Pengaruh jenis kelamin terhadap pertumbuhan kelompok potonganan atomi dan komposisi fisik karkas domba lokal=The Effect of Sex on Anatomical Primal Cut of Muscles and - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1990)
The study was conducted from October 1986 to December 1987 at the Faculty of Animal Husbandry GMU, to investigate the anatomical primal cut of muscles and carcass physical composition of local sheep, especially for carcass tissue growth. Sixteen (16) local sheep were used in this study, and consisting of 8 male and 8 female, respectively. The animals were kept in individual pen, and were given field grass and water ad libitum, added with concentrate. The weighing was done weekly. The data were collected from continous killing with the average killing-weight of 10.0 kg, 11.5 kg, 13.0 kg and 14.5 kg, respectively. The carcass were split down the midline into two sides. Each side was then followed by cutting into seven anatomical primal cut, namely neck, shoulder, rib, loin, long leg, breast, and shank, respectively, and followed by separating the bone, muscle, fat and fascia. The growth development was estimated by using an alometric wquation of Y aXb or log Y = log a + b log X. The results indicated that there were not significant changes between the primal cut obtained and the carcass growth